PENGARUH KUALITAS PELAYANAN TERHADAP HARGA DAN KEPUASAN YANG SYARâI PEMEGANG POLIS ASURANSI SYARIAH DI KODYA PROVINSI JAWA TENGAH - Koentjoro, Wuryanti (PRESTASI, 2009)
The purpose of this article is to investigate the effect of perceptionâs service quality, on price and customerâs syarâI satisfaction at Shariah life insurance in Central Java Province. The population are Shariah life insurance staff The respondents are chosen by using accidental sampling techniques. The data collected from 140 respondents and analysed by statistical tool of structural equation modeling (SEM).The result showed that : First, perception of service quality produced a positive significant impact on price. Second, price was positive and significantly associated with customerâs satisfaction.. Third, the service quality was directly related to customerâs satisfaction but the effect of service quality on customerâs satisfaction more than price as intervening variable with estimate value 0,767 if compared the directly related service quality on lsatisfaction, with value 0,277 Theoretical found that the conventional ServQual is a part from Shariah insurance study, the Shariah insurance as an alternative for customer will be faithful to the religion norm in accordance with Shariah principles. The empirical found that as Shariah insurance customers, the customers have already executed the religion norm in accordance with Al.Quran at An-Nisa:9. Studies found that the societyâs Interest to buy Shariah life insurance policy and the insurance commitment to the risk protecting are low, finally the society commitment toward life insurance decreases. Key words :Â Â Â Â  service quality/khidmah, price/tabarru,â the syarâI satisfaction /qonaâah